1976
DOI: 10.1159/000136589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Compound Action Potential and Refractory Periods of Toad Sciatic Nerve

Abstract: The action of ethanol on compound action potential, refractory periods and chronaxia are analyzed in 28 isolated sciatic nerves of toads. 85 mM ethanol increases the compound action potential and decreases the refractory periods. 342 and 513 mM ethanol decrease the compound action potential and increase the absolute and relative refractory periods. These biphasic effects are discussed in relation with changes in Na+ and K+ permeabilities and to the greater sensitivity of thin fibers to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The breakdown of the accommodation curves observed in nerves by Sato (9), Quevedo et al (6), Quevedo and Concha (7) and Vivaldi et al (10) was interpreted as the successive stimulation of two different types of fibers: low-threshold, large fibers which have higher accommodation and which would be respon sible for the first branch of the curve; the second branch would be originated by stimula tion of high-threshold, thinner fibers with lower accommodation. In normal subjects the slope of the first branch should be larger than the slope of the second branch (table I).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The breakdown of the accommodation curves observed in nerves by Sato (9), Quevedo et al (6), Quevedo and Concha (7) and Vivaldi et al (10) was interpreted as the successive stimulation of two different types of fibers: low-threshold, large fibers which have higher accommodation and which would be respon sible for the first branch of the curve; the second branch would be originated by stimula tion of high-threshold, thinner fibers with lower accommodation. In normal subjects the slope of the first branch should be larger than the slope of the second branch (table I).…”
Section: Discussionmentioning
confidence: 93%
“…Since ethanol decreases the axon membrane potential and also the sodium and potassium conductance of the axon membrane (1,5,6), ethanol should produce changes in nerve ac commodation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of ethanol on the frog sciatic nerve excitability are generally biphasic (2,5,7,8). Our results showed that ethanol increased the accommodation index of the sciatic nerve when accommodation was elicited by an expo nentially rising current of high time constant ( fig.…”
Section: Discussionmentioning
confidence: 52%